High-purity TA8 titanium ingot material prepared from TA9-1 and Gr.17 and preparation method of high-purity TA8 titanium ingot material
By using TA9-1 and Gr.17 block materials, sponge titanium and TiO2, the feeding ratio is accurately calculated and electron beam cold bed furnace smelting is solved, and the problem of reuse of low-oxygen titanium palladium alloy blocks is achieved, and the preparation of high-purity TA8 titanium ingots is improved, and the oxygen content and uniform distribution of elements are improved.
Patent Information
- Application Number
- CN202411728256.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to effectively reuse low-oxygen titanium palladium alloy bulk materials, traditional smelting methods cannot effectively control the oxygen content and inclusions, and it is difficult to achieve uniform fusion and precise adjustment of the oxygen content directly by adding TiO2 powder, resulting in a large amount of valuable bulk materials resources being wasted.
Using TA9-1 and Gr.17 blocks, sponge titanium and TiO2, by accurately calculating the feeding ratio, TiO2 is added to sponge titanium and mixed, pressed into electrode blocks, uniformly clothed with TA9-1 and Gr.17 blocks, and smelted with electron beam cold bed furnace to achieve an increase in oxygen content and uniform distribution of elements.
The O element in the low-oxygen titanium palladium alloy bulk material was effectively increased from 0.05 wt.% to 0.12~0.20 wt.%, and the Pd element was diluted from 0.135 wt.% to 0.04~0.08 wt.%, realizing the reuse of two low-oxygen titanium palladium alloy bulk materials, TA9-1 and Gr.17, and preparing high-purity large-size TA8 titanium ingots that meet market demand.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare metal material processing, and specifically relates to a high-purity TA8 titanium ingot prepared by using TA9-1 and Gr.17 and a preparation method thereof. Background Art
[0002] Palladium is commonly known as palladium, with the element symbol Pd, atomic weight 106, melting point 1554℃, belonging to the fifth period VIII platinum group elements, similar in appearance to platinum, Mohs hardness 4.75, slightly harder than platinum. The reserves of palladium in the earth's crust are less than 1 / 6 of platinum, and the global annual output is less than 8‰ of gold. Palladium is resistant to high temperature, corrosion and wear, has stable chemical properties, and is insoluble in hydrofluoric acid, perchloric acid, hydrochloric acid and cold sulfuric acid; palladium has good ductility and plasticity, and is an indispensable key material in high-tech fields such as aerospace, navigation, nuclear energy, and petrochemicals. Titanium-palladium alloy has good ductility, corrosion resistance and plasticity, and is easy to be forged, rolled, rolled and wired for deep processing. The products are mainly used in reactors, towers, autoclaves, heat exchangers, valves, pumps, centrifuges, separators, pipe fittings, electrolytic cells, etc. in strong corrosive environments such as nuclear energy and ships, and are widely used. A large amount of bulk materials will be generated during the deep processing of the above-mentioned equipment. Since this grade of titanium alloy contains palladium, it is very expensive. Therefore, the recycling of palladium-containing titanium alloy bulk materials is very valuable.
[0003] A large number of block materials are produced in the daily production process of the industry, among which Gr.6, Gr.16, TA8 and TA9 are high-oxygen materials, and the O element is in the range of 0.12wt.%≤O≤0.25wt.%. The block materials are then used to smelt the same brand of ingots, and the O element can still meet the range of 0.12wt.%≤O≤0.25wt.%. The downstream products of high-oxygen titanium-palladium alloys are in great demand, meet multiple standards, and have strong product compatibility, especially the plate market demand. Therefore, these four block materials can be separately VAR or EB smelted to recover ingots, and then rolled into plates for sale; Gr.7, Gr.17, TA8-1, and TA9-1 are low-oxygen products, with an O element of ≤0.08wt.%. Due to the excellent ductility and plasticity of low-oxygen products, they are mainly thin plates, thin tubes, and other product types. Such products are explicitly not allowed to add residual materials to prevent inclusions and oxygenation, which will affect the performance. As a result, the block materials of Gr.7, Gr.17, TA8-1, and TA9-1 produced in the daily production process of the industry are difficult to reuse. Even if the ingots obtained by bundling consumable electrodes + VAR smelting or EB smelting using traditional processes cannot be manufactured into corresponding products for sale. If powdered TiO is directly added to the block material, 2 , TiO 2 It is difficult to evenly blend with bulk materials, and it is very easy to cause the titanium dioxide to be scattered and fly during processing, as well as powdered TiO2 Due to the loss phenomenon such as being sucked away by the vacuum pump, it is impossible to achieve an increase in the O content and a uniform distribution of elements; according to market research and review of a large number of literature, there is currently no technical solution that can be used as a reference in this field at home and abroad.
[0004] In view of the difficulty in recycling low-oxygen titanium-palladium alloy bulk materials faced by existing technologies, the traditional smelting method cannot effectively control the oxygen content and inclusions. Directly adding TiO 2 It is difficult to achieve uniform fusion and precise adjustment of oxygen content in powders, and there is currently a lack of mature technical solutions to solve this problem, resulting in a large amount of valuable bulk material resources being wasted. It is urgent to find a method for effectively reusing low-oxygen titanium-palladium alloy bulk materials (such as Gr.7, Gr.17, TA8-1, TA9-1) and preparing high-purity large-size TA8 titanium ingots that meet market demand. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a high-purity TA8 titanium ingot prepared using TA9-1 and Gr.17 and a preparation method thereof, so as to solve the technical problem of how to achieve effective recycling of low-oxygen titanium-palladium alloy block materials and prepare high-purity large-size TA8 titanium ingots that meet market demand.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing high-purity TA8 titanium ingot by using TA9-1 and Gr.17, comprising: Step 1: Perform Pd element detection on untreated TA9-1 and untreated Gr.17 respectively, and accurately classify them according to the different Pd contents; perform oil removal and saponification liquid removal, alkali washing, acid washing and dust-free drying in sequence to obtain TA9-1 block material and Gr.17 block material; Step 2: Calculate the TA9-1 bulk material, Gr.17 bulk material, titanium sponge and TiO required for high purity TA8 titanium ingot according to the target composition. 2 quality; Step 3: According to the mass calculated in step 2, TiO 2 Add it to the titanium sponge, mix it, and press it into an electrode block; then evenly distribute it with the corresponding mass of TA9-1 block material and Gr.17 block material obtained in step 1, and after smelting, obtain high-purity TA8 titanium ingot.
[0007] Preferably, in step one, the surface of the TA9-1 bulk material is silvery white; the surface of the Gr.17 bulk material is silvery white; and when detecting the Pd element, a PMI handheld spectrum sorter is used for detection.
[0008] Preferably, in step one, the conditions for degreasing and desaponifying the liquid are: using a metal cleaning agent to soak at 55-65°C for 20 minutes for degreasing and desaponifying the liquid; the conditions for alkali washing are: mixing sodium hydroxide and sodium nitrate in a mass ratio of 20:1 to obtain an alkali solution, heating to a molten state, and alkali washing at 500°C for 15-30 minutes; the conditions for acid washing are: mixing water, nitric acid and hydrofluoric acid in a mass ratio of 96:2.7:1 to obtain an acid solution, and acid washing at room temperature for 15-30 minutes.
[0009] Preferably, in step 2, TA9-1 block material, Gr.17 block material, titanium sponge and TiO 2 The mass ratio is (400~510):(550~700):(400~450)(3.53~3.59).
[0010] Preferably, in step 3, TiO 2 Powdered TiO 2 ; The particle size of sponge titanium is 0.83~25.4mm.
[0011] Preferably, in step three, a 50-80MN electrode block press is used for pressing; when laying the materials, the TA9-1 block materials and Gr.17 block materials are evenly laid in layers along the axial direction of the material box.
[0012] Preferably, in step three, when laying the materials, the cross-sectional ratio of TA9-1 block material to Gr.17 block material is (1.62~1.67):1.
[0013] Preferably, in step three, during smelting, an electron beam cooling hearth furnace is used for smelting.
[0014] Preferably, in step three, after obtaining the high-purity TA8 titanium ingot, it is detected whether the mass percentage of the Pd element is 0.04-0.08wt.%; whether the mass percentage of Fe is ≤0.30 wt.%; whether the mass percentage of H is ≤0.015 wt.%; whether the mass percentage of N is ≤0.03 wt.%; whether the mass percentage of C is ≤0.08 wt.%; and whether the mass percentage of O is ≤0.25 wt.%.
[0015] The present invention also discloses a high-purity TA8 titanium ingot, which is prepared by the above method, and has an O element content of 0.12-0.20 wt.%, and a Pd element content of 0.04-0.08 wt.%.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing high-purity TA8 titanium ingots by using TA9-1 and Gr.17. Aiming at the blank of existing industrial production technology, the TA9-1, Gr.17 block material, sponge titanium and TiO are calculated according to the target composition. 2 The ratio of powdered TiO 2 Mix evenly with titanium sponge and press into electrode blocks, evenly distribute with a certain proportion of TA9-1 and Gr.17 block materials in the material box, smelt, and add TiO 2 The method effectively increases the O element in the two low-oxygen titanium-palladium alloy bulk materials from 0.05wt.% to 0.12~0.20wt.%, and dilutes the Pd element in the high-palladium TA9-1 from 0.135wt.% to 0.04~0.08wt.%, so that the two low-oxygen titanium-palladium alloy bulk materials TA9-1 and Gr.17 can be reused at the same time, and a large-size TA8 titanium ingot whose composition meets the national standard GB / T 3620.1-2016 and is easily accepted by the market is prepared. The present invention pioneered the use of two grades of titanium-palladium alloy bulk materials, sponge titanium and TiO 2 According to the target ingot composition, the feed ratio is accurately calculated, and another new grade of ingot is obtained by smelting, which provides a new process route and recycling direction for the reuse of different grades of bulk materials, and can be extended to the field of remelting and reuse of other types of bulk materials; it solves the problem that the bulk materials cannot be directly added with TiO 2 To solve the problem of oxygenation, a certain amount of powdered TiO 2 It is added to titanium sponge and mixed to make electrode blocks. After the high-oxygen electrode blocks and low-oxygen block materials are smelted, the oxygen content of the entire ingot is increased. TA8 titanium ingots are prepared by EB smelting, and the liquid metal obtains sufficient residence time and superheat in the cooling bed, and the O and Pd elements diffuse rapidly in the Ti matrix under high temperature to achieve a uniform distribution state; in addition, the impurity elements and inclusions in the material evaporate or decompose, float or sink, so as to achieve the impurity removal effect, and the evenly mixed liquid metal flows into the crystallizer for solidification, and high-purity TA8 titanium ingots are obtained after cooling, and two titanium-palladium block materials with different Pd contents and difficult to directly use are effectively recovered and remelted to obtain high-purity TA8 titanium ingots with stable quality; the large-scale TA8 titanium-palladium alloy ingots obtained by the present invention meet the national standards in composition, have uniform structure, stable palladium content, and low impurity element content, which meet the requirements of corrosion-resistant materials such as ships, centrifuges, corrosion-resistant pipelines, and electrolytic cells; it effectively saves resources, turns waste into treasure, realizes the full utilization of precious metal resources, alleviates the pressure of tight precious metal resources, saves materials and energy, and reduces environmental pollution.
[0017] Furthermore, the surface of TA9-1 bulk material is silvery white; the surface of Gr.17 bulk material is silvery white; indicating that it has undergone good surface treatment, no oxidation or pollution, has high purity and good metallic luster, which is beneficial to subsequent processing and the performance of the final product. When detecting the Pd element, the PMI handheld spectrum sorter is used for detection; it can quickly and accurately measure the content of Pd element in the bulk material. It not only improves production efficiency, but also ensures the stability of product quality. By real-time monitoring of the Pd element content, the production process can be adjusted in time to avoid the generation of waste due to unqualified element content.
[0018] Furthermore, degreasing and de-saponifying liquid can ensure that the block material will not be contaminated or affect the processing effect due to the presence of oil or saponifying liquid during the subsequent processing. Alkaline washing and acid washing can further clean the surface, remove impurities that are difficult to remove by ordinary methods, and improve the purity of the material and its compatibility with subsequent processing procedures.
[0019] Furthermore, TiO 2 Powdered TiO 2 The particle size of titanium sponge is 0.83~25.4mm; it can ensure its uniform distribution in subsequent processing and improve the performance stability of the product.
[0020] Furthermore, a 50~80MN electrode block press is used for pressing; a high-tonnage press can ensure that the block material obtains sufficient pressure and density during the pressing process, thereby improving the density and mechanical properties of the product. In addition, high pressure can also promote the close bonding between block materials, reduce the generation of pores and cracks, and improve the overall quality and durability of the product. When laying the materials, TA9-1 block materials and Gr.17 block materials are evenly layered and laid along the axial direction of the material box; layered and evenly laid can ensure that the two block materials can be evenly mixed during the smelting process, avoiding uneven performance due to local component segregation, and can also improve smelting efficiency and reduce energy consumption and waste generation during the smelting process.
[0021] Furthermore, when laying the materials, the cross-sectional ratio of TA9-1 block material to Gr.17 block material is (1.62~1.67):1; controlling the ratio of the two block materials can reduce the generation of waste due to component fluctuations and improve production efficiency and product quality stability.
[0022] Furthermore, an electron beam cold hearth furnace (EB furnace) is used for smelting instead of the traditional vacuum arc smelting (VAR) for industrial smelting production. By taking advantage of the EB smelting advantages, high-density and low-density impurities in the bulk material are removed, thereby improving purity and quality stability.
[0023] The present invention also discloses a high-purity TA8 titanium ingot prepared by the method of preparing a high-purity TA8 titanium ingot using TA9-1 and Gr.17, wherein the content of O element is 0.12-0.20 wt.%, and the content of Pd element is 0.04-0.08 wt.%; the composition of the TA8 titanium ingot not only meets the requirements of the national standard GB / T 3620.1-2016, but also realizes the precise control of key elements such as O and Pd, thereby improving the quality and stability of the product. The prepared TA8 titanium ingot has high purity and uniform organizational structure, so that it can still maintain stable performance in harsh environments, has excellent corrosion resistance, and meets the requirements of corrosion-resistant materials such as ships, centrifuges, corrosion-resistant pipelines, and electrolytic cells. It not only alleviates the pressure of tight precious metal resources, but also reduces the mining and consumption of new resources, which is conducive to environmental protection and sustainable development. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0025] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those described herein. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0026] The present invention is described in further detail below: The present invention pioneered the calculation of TA9-1 bulk material, Gr.17 bulk material, sponge titanium and TiO by TA8 target composition without using palladium powder. 2 The mass ratio of titanium sponge and TiO 2The mixed materials are evenly mixed and pressed into electrode blocks, and then evenly distributed in the material box with a certain amount of TA9-1 block materials and Gr.17 block materials. The electron beam cooling furnace (EB furnace) is used instead of the traditional vacuum smelting (VAR) for industrial smelting production. In addition, by taking advantage of the EB smelting advantages, high-density and low-density impurities in the block materials are removed to improve the purity and quality stability. TiO is introduced by pressing titanium sponge into electrodes. 2 , effectively increasing the O content in the two low-oxygen titanium-palladium alloy bulk materials from 0.05 wt.% to 0.12~0.20 wt.%, and diluting the Pd content to 0.04~0.08wt.%, and finally preparing large-scale TA8 titanium ingots with high purity and stable quality for industrial use, whose composition meets the national standard GB / T 3620.1-2016. The present invention pioneered the transformation of two low-oxygen titanium-palladium alloy bulk materials that are difficult to directly recycle into treasure, solved the problem of oxygenation of bulk materials, realized the full utilization of precious metal resources, saved materials and energy, reduced production costs, and reduced environmental pollution; at the same time, the advantage of EB smelting in removing high and low density inclusions was used to produce large-scale TA8 ingots with high purity and stable quality.
[0027] See Table 1 for the Pd and O element content / wt.% of different grades of titanium-palladium alloys; it can be seen from the table that there are two standards for titanium-palladium alloys commonly used in the market, American standard: B265-10, grades include Gr.6, Gr.16, Gr.7, Gr.17; national standard: GB / T3620.1, grades include TA8, TA8-1, TA9, TA9-1, the specific Pd and O element contents are shown in Table 1.
[0028] Table 1 Pd and O content of different grades of titanium-palladium alloys (wt.%)
[0029] The present invention discloses a method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17, comprising the following steps: Step 1: Collect untreated TA9-1 and untreated Gr.17, screen and classify them for storage; Step 2: Use a PMI handheld spectrum sorter to detect the Pd element of the two titanium palladium materials, the untreated A9-1 and the untreated Gr.17, which were initially classified and stored in step 1, and accurately classify the two bulk materials again according to the different Pd contents; Step 3: Degrease, remove saponification liquid, alkali wash, pickle and air dry the block materials of the same brand confirmed in step 2 in turn to obtain surface-free TA9-1 block materials and Gr.17 block materials. After treatment, the surface of the block materials is silvery white; wherein, the degreasing and saponification liquid removal conditions are: metal cleaning agent is used, and the temperature is 60±5℃, so as to fully dissolve the oil and saponification liquid and avoid the volatilization of the metal cleaning agent to reduce the concentration, and the immersion time of the metal cleaning agent is 20min. The alkali washing conditions are: the reference ratio of the alkali solution is sodium hydroxide: sodium nitrate = 20:1 (weight percentage), heated for 15~30 min to about 500℃ in a molten state, and it is strictly forbidden to add water to the alkali washing tank to prevent explosion and splashing; the pickling conditions are: the reference ratio of the acid solution is water: nitric acid: hydrofluoric acid = 96:2.7:1 (weight percentage), the total amount is based on the material being submerged, and the pickling is carried out at room temperature for 15~30 min.
[0030] Step 4: Calculate the TA9-1 bulk material, Gr.17 bulk material, titanium sponge and TiO required for smelting and preparing TA8 ingot according to the target composition. 2 quality; Step 5: Select titanium sponge (particle size: 0.83~25.4mm) of standard size that meets GB / T 2524-2019, and mix a certain amount of powdered TiO 2 Add to a certain amount of titanium sponge and mix, and use a 50~80MN electrode block press to press into electrode blocks; Step 6: Evenly distribute the quantitative TA9-1 block material and Gr.17 block material processed in step 3 and the electrode block in step 5 in a material box, and use an electron beam cooling furnace (EB furnace) for smelting to obtain high-purity TA8 titanium ingots; Step 7: Sample the high-purity TA8 titanium ingot obtained in step 6 and detect the content of Pd element and impurity elements to determine whether it meets the composition requirements of TA8 in GB / 3620.1-2016 "Titanium and Titanium Alloy Grades and Chemical Compositions", as shown in Table 2.
[0031] Table 2 Composition requirements of TA8 in GB / 3620.1-2016 "Titanium and titanium alloy grades and chemical composition"
[0032] The present invention has no technical route for reference. First, untreated TA9-1 and untreated Gr.17 block materials are classified and collected. The PMI handheld spectrum sorter is used to confirm the grades of the collected untreated TA9-1 and untreated Gr.17 block materials respectively to prevent other grades of metals from mixing in. After two chemical treatments of alkali washing and acid washing, oxides and pollutants on the surface of the block materials are removed. Then, the alkali and acid residues on the surface of the block materials are washed with clean water, and then the block materials are dried without dust to obtain two block materials of TA9-1 block materials and Gr.17 block materials with no pollution on the surface. According to the composition of the two block materials and the target ingot composition, the sponge titanium and TiO 2 The addition ratio of TA9-1 block material and Gr.17 block material is calculated according to the proportion of titanium sponge and TiO 2 Mix and compress into electrode blocks, evenly distribute with TA9-1 block materials and Gr.17 block materials in the material box, and evenly lay TA9-1 block materials and Gr.17 block materials in layers along the axial direction of the material box to ensure that the cross-sectional composition is basically consistent; then carry out EB smelting, the liquid metal obtains sufficient residence time and superheat in the cooling bed under high vacuum conditions, and the O and Pd elements diffuse rapidly in the Ti matrix at high temperature to achieve a uniform distribution state; in addition, the impurity elements and inclusions in the block materials evaporate or decompose, and the high-density inclusions sink, achieving the effect of impurity removal. The evenly mixed liquid metal flows into the crystallizer to solidify, and after cooling, a high-purity TA8 titanium ingot is obtained, which effectively recycles and remelts the two titanium palladium block materials with different Pd contents and difficult to directly use, and obtains a titanium palladium alloy grade titanium ingot with a wide range of uses and easy to sell.
[0033] In the preferred embodiment of the present invention, a PMI handheld spectrum sorter is used to detect the Pd element in two titanium palladium bulk materials, untreated TA9-1 and untreated Gr.17, and the two bulk materials are classified and stored according to the different Pd element contents.
[0034] In the preferred embodiment of the present invention, the TA9-1 block material, Gr.17 block material, sponge titanium and TiO required for smelting and preparing TA8 titanium ingot are calculated according to the target composition. 2 The ratio of the powdered TiO 2 Add it into titanium sponge and mix it, and use a 50~80MN electrode block press to press it into electrode blocks.
[0035] In the preferred embodiment of the present invention, the pressed electrode blocks and TA9-1 block materials and Gr.17 block materials are evenly distributed in the material box, and the TA9-1 block materials and Gr.17 block materials are evenly layered and laid along the axial direction of the material box to ensure that the cross-sectional components are basically consistent. The cross-sectional ratio of TA9-1 block materials and Gr.17 block materials is (1.62~1.67):1.
[0036] In the preferred embodiment of the present invention, EB melting (electron beam cold hearth melting) is adopted, and the liquid metal obtains sufficient residence time and superheat in the cold hearth under high vacuum conditions, and the O and Pd elements diffuse rapidly in the Ti matrix at high temperature to achieve a uniform distribution state; in addition, the impurity elements and inclusions in the block material evaporate or decompose, float or sink, so as to achieve the impurity removal effect, and the evenly mixed liquid metal flows into the crystallizer to solidify, and TA8 titanium ingots are obtained after cooling.
[0037] Example 1 A method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17, comprising the following steps: Step 1: Collect untreated TA9-1 and untreated Gr.17, screen and classify them for storage; Step 2: Use a PMI handheld spectrum sorter to detect the Pd element of the two titanium palladium bulk materials, untreated TA9-1 and untreated Gr.17, which were initially classified and stored in step 1, and accurately classify the two bulk materials again according to the different Pd contents; Step 3: Degrease, remove saponification liquid, alkali wash, pickle and air-dry the block materials of the same brand confirmed in step 2 in turn to obtain surface-free TA9-1 block materials and Gr.17 block materials, and the surface of the block materials is silvery white; the conditions for degreasing and removing saponification liquid are: immerse in a metal cleaning agent at 55°C for 20 minutes for degreasing and removing saponification liquid; the conditions for alkali washing are: mix sodium hydroxide and sodium nitrate in a mass ratio of 20:1 to obtain alkali solution, heat to a molten state, and alkali wash at 500°C for 15 minutes; the conditions for pickling are: mix water, nitric acid and hydrofluoric acid in a mass ratio of 96:2.7:1 to obtain acid solution, and pickle at room temperature for 15 minutes; Step 4: Calculate the TA9-1 bulk material, Gr.17 bulk material, sponge titanium and TiO required for smelting and preparing TA8 titanium ingot according to the target composition. 2 The quality of ingredients. The O element of the ingot meets the range of 0.12~0.20 wt.%, and the ingredient value is 0.150 wt.%; the Pd element meets the range of 0.04~0.08 wt.%, and the ingredient value is 0.058 wt.%. After calculation, the amount of sponge titanium for each ingot is 450 kg, the amount of titanium dioxide is 3.59 kg, and the standard particle size sponge titanium (particle size: 0.83~25.4 mm) that meets the standard GB / T 2524-2019 is selected. A total of 7 electrode blocks are pressed, and the weight of a single block is 65.51 kg. The O element ingredient value of a single electrode block is 0.351 wt.%, of which the oxygen content of sponge titanium is subject to the inspection results of the sponge titanium manufacturer. Sponge titanium and TiO 2 After uniform mixing, the materials are pressed into electrode blocks using a 50MN electrode block press (see Table 3 for specific ingredients); Table 3 Ingredients of 1# Ingot
[0038] Step 5: Evenly spread the 7 electrode blocks along the axial direction at the bottom of the material box. Evenly spread a certain proportion of Gr.17 block materials and TA9-1 block material strips along the axial direction to ensure that the cross-sectional composition is basically consistent. The cross-sectional ratio of TA9-1 block materials and Gr.17 block materials is about 1.62:1. It is strictly forbidden to gather and place strips of the same brand in a part of the material box to prevent uneven composition. Step 6: After the material is laid in step 5, it is melted in an EB electron beam cooling furnace to obtain a round ingot with a diameter and length of 380 mm × 2800 mm. The specific process of EB melting is as follows: before melting, the furnace of the electron beam cooling furnace is thoroughly cleaned to remove adhesions, volatiles and oil stains around the material, the cooling bed and the crystallizer as much as possible, and the vacuum degree in the furnace is evacuated to less than 5.0×10 -3 torr and the gas leakage rate is qualified, EB smelting is carried out according to the process flow and smelting parameters in Table 4; Table 4 Process flow and smelting parameters
[0039] When increasing the current during EB smelting, pay close attention to the changes in the vacuum degree in the furnace, adjust the current value of each gun in time to avoid a sharp drop in the vacuum degree in the furnace in a short time, adjust the scanning trajectory and position of the 1# electron gun to avoid the block chips being melted in advance, the electron beam damaging the cooling bed, and the bottom making stage not being cooled after completion; during normal smelting, reasonably adjust the scanning pattern of the 2# electron gun to ensure that there is no cold zone in the cooling bed, and control the feeding speed, melting speed, and ingot pulling speed to make them well matched; during normal smelting, reasonably adjust the scanning pattern of the 3# electron gun. The role of the 3# gun is to keep the liquid level in the circular crystallizer warm and replenish energy, maintain the temperature thermal field of the crystallization area above the ingot, and avoid the solution from flowing from the cooling bed into the crystallizer and solidifying instantly due to the low temperature to produce metallurgical defects such as pores, scars, and cold shuts.
[0040] Step 7: Sampling the round ingot obtained in step 6, including block samples and chip samples, the sampling positions are 200-300 mm from the riser end of the round ingot, 200-300 mm from the middle and 200-300 mm from the bottom, and the composition is tested according to the requirements of GB / T3620.1-2016 "Titanium and Titanium Alloy Grades and Chemical Compositions", and the results are shown in Table 5; Table 5 Chemical composition test results of 1# ingot / wt.%
[0041] From the composition test results, it can be seen that the contents of O, Pd and other impurity elements in the 1# ingot obtained after EB smelting meet the requirements of TA8 in GB / T 3620.1-2016 "Titanium and Titanium Alloy Grades and Chemical Compositions", and the Pd element composition is uniform.
[0042] Example 2 A method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17, comprising the following steps: Step 1: Collect untreated TA9-1 and untreated Gr.17, screen and classify them for storage; Step 2: Use a PMI handheld spectrum sorter to detect the Pd element of the two titanium palladium bulk materials, untreated TA9-1 and untreated Gr.17, which were initially classified and stored in step 1, and accurately classify the two bulk materials again according to the different Pd contents; Step 3: Degrease, remove saponification liquid, alkali wash, pickle and air-dry the block materials of the same brand confirmed in step 2 in turn to obtain surface-free TA9-1 block materials and Gr.17 block materials, and the surface of the block materials is silvery white; the conditions for degreasing and removing saponification liquid are: use a metal cleaning agent to soak at 60°C for 20 minutes for degreasing and removing saponification liquid; the conditions for alkali washing are: sodium hydroxide and sodium nitrate are mixed in a mass ratio of 20:1 to obtain alkali solution, heated to a molten state, and alkali washed at 500°C for 20 minutes; the conditions for pickling are: water, nitric acid and hydrofluoric acid are mixed in a mass ratio of 96:2.7:1 to obtain acid solution, and pickling at room temperature for 20 minutes; Step 4: Calculate the TA9-1 bulk material, Gr.17 bulk material, sponge titanium and TiO required for smelting and preparing TA8 titanium ingot according to the target composition. 2 The O element of the ingot meets the range of 0.12 wt.%~0.20 wt.%, and the ingredient value is 0.150 wt.%; the Pd element meets the range of 0.04 wt.%~0.08 wt.%, and the ingredient value is 0.065 wt.%. After calculation, the amount of sponge titanium for each ingot is 440 kg, the amount of titanium dioxide is 3.53 kg, and the standard particle size sponge titanium (particle size: 0.83~25.4 mm) that meets the standard GB / T 2524-2019 is selected. A total of 7 electrode blocks are pressed, with a single block weight of 63.36 kg. The O element ingredient value of a single electrode block is 0.343 wt.%, of which the oxygen content of sponge titanium is subject to the inspection results of the sponge titanium manufacturer. Sponge titanium and TiO 2 After uniform mixing, use 8000T press to press into electrode blocks (see Table 6 for specific ingredients) Table 6 Ingredients of 2# Ingot
[0043] Step 5: Evenly spread the 7 electrode blocks at the bottom of the material box along the axial direction. Evenly spread a certain proportion of Gr.17 block materials and TA9-1 block material strips in layers along the axial direction to ensure that the cross-sectional composition is basically consistent. The cross-sectional ratio of TA9-1 block materials and Gr.17 block materials is about 1.6:1. It is strictly forbidden to gather and place strips of the same brand in a part of the material box to prevent uneven composition. Step 6: After the material is laid in step 5, it is melted in an EB electron beam cooling furnace to obtain a round ingot with a diameter and length of 380 mm × 2800 mm. The specific process of EB melting is as follows: before melting, the furnace of the electron beam cooling furnace is thoroughly cleaned to remove adhesions, volatiles and oil stains around the material, the cooling bed and the crystallizer as much as possible, and the vacuum degree in the furnace is evacuated to less than 5.0×10 -3 torr and the gas leakage rate is qualified, EB smelting is carried out according to the process flow and smelting parameters in Table 4; When increasing the current during EB smelting, pay close attention to the changes in the vacuum degree in the furnace, adjust the current value of each gun in time to avoid a sharp drop in the vacuum degree in the furnace in a short time, adjust the scanning trajectory and position of the 1# electron gun to avoid the block chips being melted in advance, the electron beam damaging the cooling bed, and the bottom making stage not being cooled after completion; during normal smelting, reasonably adjust the scanning pattern of the 2# electron gun to ensure that there is no cold zone in the cooling bed, and control the feeding speed, melting speed, and ingot pulling speed to make them well matched; during normal smelting, reasonably adjust the scanning pattern of the 3# electron gun. The role of the 3# gun is to keep the liquid level in the circular crystallizer warm and replenish energy, maintain the temperature thermal field of the crystallization area above the ingot, and avoid the solution from flowing from the cooling bed into the crystallizer and solidifying instantly due to the low temperature to produce metallurgical defects such as pores, scars, and cold shuts.
[0044] Step 7: Sampling the round ingot obtained in step 6, including block samples and chip samples, the sampling positions are 200-300 mm from the riser end of the round ingot, 200-300 mm from the middle and 200-300 mm from the bottom, and the composition is tested according to the requirements of GB / T3620.1-2016 "Titanium and Titanium Alloy Grades and Chemical Compositions", and the results are shown in Table 7; Table 7 Chemical composition test results of 2# ingot / wt.%
[0045] From the composition test results, it can be seen that the contents of O, Pd and other impurity elements in the 2# ingot obtained by EB smelting meet the requirements of TA8 in GB / T3620.1-2016 "Titanium and Titanium Alloy Grades and Chemical Compositions", and the Pd element is evenly distributed. After adjusting the feed ratio, the O element is reduced compared with Example 1, and the actual value of the Pd element content is increased.
[0046] Example 3 A method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17, comprising the following steps: Step 1: Collect untreated TA9-1 and untreated Gr.17 bulk materials, screen and classify them for storage; Step 2: Use a PMI handheld spectrum sorter to detect the Pd element of the two titanium palladium bulk materials, untreated TA9-1 and untreated Gr.17, which were initially classified and stored in step 1, and accurately classify the two bulk materials again according to the different Pd contents; Step 3: Degrease, remove saponification liquid, alkali wash, pickle and dust-free dry the block materials of the same brand confirmed in step 2 in turn to obtain surface-free TA9-1 block materials and Gr.17 block materials, and the surface of the block materials is silvery white; the conditions for degreasing and removing saponification liquid are: immerse in a metal cleaning agent at 65°C for 20 minutes for degreasing and removing saponification liquid; the conditions for alkali washing are: mix sodium hydroxide and sodium nitrate in a mass ratio of 20:1 to prepare alkali solution, heat to a molten state, and alkali wash at 500°C for 30 minutes; the conditions for pickling are: mix water, nitric acid and hydrofluoric acid in a mass ratio of 96:2.7:1 to prepare acid solution, and pickle at room temperature for 30 minutes; Step 4: Calculate the TA9-1 bulk material, Gr.17 bulk material, sponge titanium and TiO required for smelting and preparing TA8 titanium ingot according to the target composition. 2 The O element of the ingot meets the range of 0.12 wt.%~0.20 wt.%, and the ingredient value is 0.150 wt.%; the Pd element meets the range of 0.04 wt.%~0.08 wt.%, and the ingredient value is 0.062 wt.%. After calculation, the amount of sponge titanium for each ingot is 400 kg, the amount of titanium dioxide is 3.58 kg, and the standard particle size sponge titanium (particle size: 0.83~25.4 mm) that meets the standard GB / T 2524-2019 is selected. A total of 7 electrode blocks are pressed, with a single block weight of 57.65 kg. The O element ingredient value of a single electrode block is 0.380 wt.%, of which the oxygen content of sponge titanium is subject to the inspection results of the sponge titanium manufacturer. The content of sponge titanium and TiO 2 After uniform mixing, the materials are pressed into electrode blocks using a 70MN electrode block press (see Table 8 for specific ingredients); Table 8 Ingredients of 3# Ingot
[0047] Step 5: Evenly spread the 7 electrode blocks at the bottom of the material box along the axial direction. Evenly spread a certain proportion of Gr.17 block materials and TA9-1 block material strips in layers along the axial direction to ensure that the cross-sectional composition is basically consistent. The cross-sectional ratio of TA9-1 block materials and Gr.17 block materials is about 1.67:1. It is strictly forbidden to gather and place strips of the same brand in a part of the material box to prevent uneven composition. Step 6: After the material is laid in step 5, it is melted in an EB electron beam cooling furnace to obtain a round ingot with a diameter and length of 380 mm × 2800 mm. The specific process of EB melting is as follows: before melting, the furnace of the electron beam cooling furnace is thoroughly cleaned to remove adhesions, volatiles and oil stains around the material, the cooling bed and the crystallizer as much as possible, and the vacuum degree in the furnace is evacuated to less than 5.0×10 -3 torr and the gas leakage rate is qualified, EB smelting is carried out according to the process flow and smelting parameters in Table 4; When increasing the current during EB smelting, pay close attention to the changes in the vacuum degree in the furnace, adjust the current value of each gun in time to avoid a sharp drop in the vacuum degree in the furnace in a short time, adjust the scanning trajectory and position of the 1# electron gun to avoid the block chips being melted in advance, the electron beam damaging the cooling bed, and the bottom making stage not being cooled after completion; during normal smelting, reasonably adjust the scanning pattern of the 2# electron gun to ensure that there is no cold zone in the cooling bed, and control the feeding speed, melting speed, and ingot pulling speed to make them well matched; during normal smelting, reasonably adjust the scanning pattern of the 3# electron gun. The role of the 3# gun is to keep the liquid level in the circular crystallizer warm and replenish energy, maintain the temperature thermal field of the crystallization area above the ingot, and avoid the solution from flowing from the cooling bed into the crystallizer and solidifying instantly due to the low temperature to produce metallurgical defects such as pores, scars, and cold shuts.
[0048] Step 7: Sampling the round ingot obtained in step 6, including block samples and chip samples, the sampling positions are 200-300 mm from the riser end of the round ingot, 200-300 mm from the middle and 200-300 mm from the bottom, and the composition is tested according to the requirements of GB / T3620.1-2016 "Titanium and Titanium Alloy Grades and Chemical Compositions", and the results are shown in Table 9; Table 9 Chemical composition test results of 3# ingot / wt.%
[0049] From the composition test results, it can be seen that the contents of O, Pd and other impurity elements in the 3# ingot obtained by EB smelting meet the requirements of TA8 in GB / T3620.1-2016 "Titanium and Titanium Alloy Grades and Chemical Compositions", and the Pd element is evenly distributed.
[0050] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17, characterized in that: include: Step 1: Perform Pd element detection on untreated TA9-1 and untreated Gr.17 respectively, and accurately classify them according to the different Pd contents; perform oil removal and saponification liquid removal, alkali washing, acid washing and dust-free drying in sequence to obtain TA9-1 block material and Gr.17 block material; Step 2: Calculate the mass of TA9-1 bulk material, Gr.17 bulk material, titanium sponge and TiO2 required for high-purity TA8 titanium ingot according to the target composition; Step 3: Add TiO2 to the titanium sponge according to the mass calculated in step 2, mix and press into electrode blocks; then evenly distribute with the corresponding mass of TA9-1 block material and Gr.17 block material obtained in step 1, and after smelting, obtain high-purity TA8 titanium ingots.
2. The method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17 according to claim 1, characterized in that: In step 1, the surface of the TA9-1 bulk material is silvery white; the surface of the Gr.17 bulk material is silvery white; when the Pd element is detected, a PMI handheld spectrum sorter is used for detection.
3. The method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17 according to claim 1, characterized in that: In step 1, the conditions of the degreasing and desaponifying solution are: using a metal cleaning agent to soak at 55~65℃ for 20min for degreasing and desaponifying solution; the conditions of the alkali washing are: mixing sodium hydroxide and sodium nitrate in a mass ratio of 20:1 to obtain an alkali solution, heating to a molten state, and alkali washing at 500℃ for 15~30min; the conditions of the acid washing are: mixing water, nitric acid and hydrofluoric acid in a mass ratio of 96:2.7:1 to obtain an acid solution, and acid washing at room temperature for 15~30min.
4. The method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17 according to claim 1, characterized in that: In step 2, the mass ratio of the TA9-1 bulk material, Gr.17 bulk material, sponge titanium and TiO2 is (400~510):(550~700):(400~450)(3.53~3.59).
5. The method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17 according to claim 1, characterized in that: In step three, the TiO2 is powdered TiO2; the particle size of the titanium sponge is 0.83~25.4mm.
6. The method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17 according to claim 1, characterized in that: In step three, a 50~80MN electrode block press is used for pressing; when laying the materials, the TA9-1 block material and the Gr.17 block material are evenly laid in layers along the axial direction of the material box.
7. The method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17 according to claim 1, characterized in that: In step three, when laying the materials, the cross-sectional ratio of TA9-1 block material to Gr.17 block material is (1.62~1.67):
1.
8. The method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17 according to claim 1, characterized in that: In step three, during the smelting, an electron beam cooling hearth furnace is used for smelting.
9. The method for preparing high-purity TA8 titanium ingot using TA9-1 and Gr.17 according to claim 1, characterized in that: In step 3, after obtaining high-purity TA8 titanium ingot, check whether the mass percentage of Pd element is 0.04-0.08wt.%; whether the mass percentage of Fe is ≤0.30 wt.%; whether the mass percentage of H is ≤0.015 wt.%; whether the mass percentage of N is ≤0.03 wt.%; whether the mass percentage of C is ≤0.08 wt.%; and whether the mass percentage of O is ≤0.25wt.%.
10. A high purity TA8 titanium ingot, characterized in that: The method for preparing high-purity TA8 titanium ingots using TA9-1 and Gr.17 as described in any one of claims 1 to 9 is adopted, wherein the O element content is 0.12 to 0.20 wt.%, and the Pd element content is 0.04 to 0.08 wt.%.